Tuning of PEDOT: PSS Properties Through Covalent Surface Modification; Journal of Polymer Science, Part B: Polymer Physics; Vol. 55, iss. 4 - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Premysl F. Fitl; Tomecek D. David; Sajdl P. Petr; Elashnikov R. Roman; Kolska Z. Zdenka; Chehimi M. M. Mohamed Mehdi; Svorcik V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen